The mark of tropeirism and the paths of cattle in Alagoas / A marca do tropeirismo e os caminhos do gado em Alagoas - José Robson Gonçalves Ferreira; Angela Maria Araújo Leite (Universidade Estadual de Alagoas, 2020)
Plantation, in northeastern Brazil, is introduced after the Portuguese invasion in the early sixteenth century. The cultivation of sugarcane will be inserted into the forest área anf the mills are spreading through the sugar cane territory. To support these mills, food production will develop in the wild and cattle ranching in the hinterland, thus the interior is being occupied, especially in the current Alagoas territory. It will be from this approach that this work will develop. The objective is to presente results of the frist stage of a research on the formation of cities, through documentar surveys in notaries, churches and public agencies. Thus, it was verified the importance of tropeirismo, which will be fundamental for the emergence of free fairs and, consequently, of the cities of the wild. Similarly, cattle farms will be the initial milestone of the occupation of the municipalities of the Alagoas hinterland.